PENGEMBANGAN APLIKASI ANDROID ONE DAY ONE JUZ (ODOJ) MENGGUNAKAN METODE EXTREME PROGRAMMING - Muhammad Arief Hidayat; Dwi Sakethi; Ardiansyah Ardiansyah (Jurnal Pepadun, 2022)
The ODOJ program that utilizes instant messaging applications such as Whatsapp and Telegram cannot handle the recording of "Tilawatil Quran" every juz per day. This study seeks to develop an Android-based ODOJ application that can assist Muslims in conducting the ODOJ program, especially in the process of reporting and recording recitations. Data used in this study was obtained by means of observation, interviews, and literature studies. The system development method chosen in this research is the Extreme Programming development method. This system is built based on android, the programming process (coding) uses the Kotlin programming language with firebase as the database. The test in this study uses Black-Box testing with the Equivalence Partitioning (EP) method. The results of the tests that have been carried out show that the system can function according to user needs and the results of theuser acceptance test of the system are in the very good category.